Library Space Utilization in Secondary Schools: A Case Study of Kabale Trinity College in Southern Division. - Agumenaitwe, Priva (Kabale University, 2024)
The study holds significant implications for various stakeholders involved in secondary education and library management. Understanding how library spaces are utilized and the factors influencing their usage will aid decision-making processes aimed at enhancing educational resources and student learning experiences. The study was guided by three specific objectives: assess how library spaces are currently being utilized at Kabale Trinity College, identify the factors affecting library space utilization at Kabale Trinity College, and suggest improvements for optimizing library spaces at Kabale Trinity College.